E-004 The utility of micro vascular plug in the treatment embolization of vein of galen malformation: a case report, technical consideration, and literature review. (22nd July 2019) - Mathkour, M; McCormack, E; Berry, J; Dumont, A; Valle-Giler, E
Abstract : Background: Vein of Galen malformations (VOGM) are rare, accounting in recent literature for approximately thirty percent of pediatric venous malformations, caused by abnormal venogensis during gestation. VOGM is divided into two categories, mural and choroidal, depending on the respective feeding vessels. At presentation, VOGM is known to cause additional complications in the neonate including hydrocephalus, congestive heart failure, and seizures. Treatment options include coil and microparticle embolization in addition to the recent introduction of the microvascular plug used traditionally for arterial occlusion. In this case presentation, we present the second known case of use of the microvascular plug (MVP) to assist with venous occlusion for a VOGM Method/Case presentation: A 39 weeks male was born via an urgent Cesarean section for right atrial dilation, cardiac arrhythmia thought to be premature atrial complexes and a cerebral vascular malformation. His mother had had a recent fetal ultrasound demonstrating intrauterine growth restriction. Head ultrasound performed after birth demonstrated a large vein of Galen malformation. MRI with angiography and venography demonstrated a 4.3×3.6×4.1 centimeter aneurysmal VOGM with primary supply via a dilated right superior cerebellar artery and primary drainage via a dilated median prosencephalic vein. Intervention/Result: Postpartum day 7, the patient showed signs and symptoms of worsening heart failure. Treatment was deemed necessary. The left vertebral artery was catheterized and multiple runs performed revealing a mural type vein of Galen malformation with direct AV fistula from the supplying right superior cerebellar artery. The right superior cerebellar artery was measured at approximately 3.8 mm in diameter. A 3–5 mm Microvascular Plug device was chosen for primary embolization. Post MVP deployment angiographic runs showed decreased flow through the fistula. Three coils were then deployed followed by Onyx 34 in order to completely obliterate the fistula. Final angiographic runs revealed fistula obliteration and patent basilar artery, posterior cerebral arteries, left superior cerebellar artery and left PICA. Follow up cranial US with smaller ventricular size and repeat echocardiography with stable hemodynamics and without evidence of heart failure. Conclusion: This is the second case documented in the literature demonstrating the utility of the microvascular plug for assistance in embolization of a VOGM. The utility of this device is limited by vessel diameter and appropriate landing zone requirements. Further investigation is needed to assess feasibility as well as short and long term outcomes and possible related complications from embolization including postoperative development of hydrocephalus which common in both our case and the previously published literature. Disclosures: M. Mathkour: None. E. McCormack: None. J. Berry: None. A. Dumont: None. E. Valle-Giler: None.